Pengelompokkan Ekspor Kopi Menurut Negara Tujuan Menggunakan Metode K-Means Clustering dengan Silhouette Coefficient - Suryadi Muzahidi Aziz; Nur Azizah Komara Rifai (Bandung Conference Series: Statistics, 2022)
Abstract. Indonesia is one of the coffee exporting countries that has reached five continents, namely Asia, Australia, America, and Europe. The purpose of this study is to determine which countries are included in the high coffee export cluster, and the low coffee export cluster. The method used in this research is the K-Means Clustering method with Silhouette Coefficient. The advantage of this method is that it can perform analysis of larger samples more efficiently. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS). The data contains data on the amount of coffee exports (net) and the value of FOB (Free On Board) from 2000 to 2020 in Indonesia. The software used in this research is RStudio. The results of this study conclude that, first, the K-Means Clustering Method with the Silhouette Coefficient can determine the grouping of coffee exports. The data is processed using the silhouette method which in its processing determines the value of k whose results are known to be 2 clusters, so the data to be taken is a high export level cluster, and a low export level cluster. Second, the data centroids for the high export level cluster are Japan, the United States and Germany. Third, the data centroids for the low export level cluster are Singapore, Malaysia, India, Egypt, Morocco, Algeria, England, Italy, Romania, Georgia, Belgium, the Netherlands, Denmark, and France. Fourth, the Silhoutte coefficient value that can be known is 0.73, where 0.7 < SI <= 1 is a strong structure cluster, so coffee export groupings have very good quality because of their high value. Abstrak. Indonesia menjadi salah satu negara pengekspor komoditi kopi yang telah menjangkau lima benua, yaitu Asia, Australia, Amerika, dan Eropa. Tujuan penelitian ini adalah menentukan negara yang termasuk ke dalam cluster ekspor kopi tinggi, dan cluster ekspor kopi rendah. Metode yang digunakan pada penelitian ini adalah metode K-Means Clustering dengan Silhouette Coefficient. Kelebihan metode ini adalah dapat melakukan analisis sampel dalam ukuran yang lebih besar dengan lebih efisien. Data yang digunakan dalam penelitian ini adalah data Sekunder yang di peroleh dari Badan Pusat Statistik (BPS). Data tersebut berisi data mengenai Jumlah ekspor kopi (netto) dan nilai FOB (Free On Board) dari tahun 2000 sampai 2020 di Indonesia. Software yang digunakan pada penelitian ini adalah RStudio. Hasil penelitian ini menyimpulkan bahwa, pertama, Metode K-Means Clustering dengan Silhouette Coefficient dapat menentukan pengelompokkan ekspor kopi. Data diolah dengan menggunakan metode silhouette yang dimana dalam pengolahan nya menentukan nilai k yang hasil nya diketahui 2 cluster, makan data yang akan di ambil adalah cluster tingkat ekspor tinggi, dan cluster tingkat ekspor rendah. Kedua, Centroid data untuk cluster tingkat ekspor tinggi adalah Negara Jepang, Amerika Serikat dan Jerman. Ketiga, Centroid data untuk cluster tingkat ekspor rendah adalah Negara Singapura, Malaysia, India, Mesir, Maroko, Aljazair, Inggris, Italia Rumania, Georgia, Belgia, Belanda, Denmark, dan Perancis. Keempat, Nilai Silhoutte coefficient yang dapat diketahui adalah 0.73 yang mana 0.7 < SI <= 1 merupakan cluster strong scructure jadi pengelompokan ekspor kopi mempunyai kualitas yang sangat baik karena nilai nya tinggi